Polymeric films for wounds management: a review (Research, Society and Development, 2022)
Objective: To seek evidence on the performance of polymeric films in the treatment of wounds, gathering scientific articles in which tests that assess the quality and efficiency of polymeric films in the management of wounds have been performed. Methodology: A narrative review of a qualitative nature was carried out, following the recommendations of the Cochrane Collaboration in an adapted way, in Pubmed and Capes Periodicals, including studies produced in the last five years, without language restriction. Result: In total, 7 studies were included, which brought important data on the good performance of polymeric films in the wound healing process. Final considerations: Polymers allow the production of resistant, flexible, transparent, biocompatible polymeric films, allowing the incorporation of actives and with the ability to absorb exudates, in addition to having low cost. They demonstrated excellent results in the treatment of the tested wounds promoting faster healing compared to controls. Incorporating the good properties of these materials into clinical and physiological knowledge makes it possible to use a more advanced and efficient approach to wound care, making the healing process more comfortable and functional for the patient.